Do divino ao mortal : variações nas representações das Musas na literatura grega dos períodos arcaico e clássico - Ívina Silva Guimarães (2021)
The current work proposes to present and analyze aspects of the Muses’ representations in the literary works of the archaic and classical periods of ancient Greece. One of the purposes of the study is to understand the appropriations of the goddesses and the variations in their functions and image according to each epoch, literary genre or aspect of thought. For achieving this goal, the appearances of the Muses in literature are mapped according to categories that contribute to a certain definition of the Muses’ identity. The categories created are: Nomenclature, Visual and Auditory Attributes, Invocation, Functions, and Associated Places. From the presentation of the sources classified in the different categories, such data are analyzed in view of the permanences and variations between the selected works and authors. At the end, hypotheses are elaborated that seek to answer some of the questions developed during the research. Among the aspects that highlight in the analysis of sources, the variation in visual and auditory characterizations, and in the functions assigned to the Muses draw attention due to their diverse content. Founded on works and authors from different historical periods and literary genres, such variations point to possible changes in the social and cultural practices of archaic and classical Greece.